Efficacy of titanium brush, 915 nm diode laser, citric acid for eradication of Staphylococcus aureus from implant surfaces - Mohammad Reza Karimi; Behshad Farkhondemehr; Motahare Ghaeni Najafi; Ardavan Etemadi; Nasim Chiniforush (BMC, 2021)
Abstract Background This study aimed to assess the efficacy of titanium brush, 915 nm diode laser, citric acid and the combination of latter two with titanium brush for decontamination of SLA surface mini-implants. Methods Seventy-five mini-implants contaminated with Staphylococcus aureus (S. aureus) were randomly divided into five experimental groups (n = 12) of titanium brush (TiB), laser, citric acid (CA), brush-laser, and brush-acid, positive [n = 12; chlorhexidine mouthwash (CHX)] and negative [n = 2; phosphate buffered saline (PBS)] control groups and one no-treatment group (n = 1). After counting the colony forming units (CFUs), data were analyzed using the Kruskal-Wallis and Dunn post-hoc tests. Results Regardless of the no-treatment and negative control groups, maximum and minimum CFUs were noted in the titanium brush and positive control groups. After CHX, minimum CFUs were noted in brush-acid group followed by brush-laser, laser, and acid groups. Generally, the Kruskal-Wallis test revealed a significant difference between the groups regarding the colony count (P < 0.001). Dunn post-hoc test showed that the difference between the titanium brush and acid-brush group was significant (P < 0.001) while the differences between the brush and laser groups with the brush-laser group were not significant (P > 0.077). Conclusions Combined use of titanium brush and citric acid yielded superior results compared to other groups in reduction of S. aureus on implant surface.